Association between D-Dimer and CRP Levels in Confirmed COVID-19 Patients with Diabetes Mellitus Comorbidity at Jakarta Hajj Hospital - Atna Permana; Adik Purnama; Warida Warida; Haitami Haitami (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
COVID-19 may induce systemic inflammation and coagulation abnormalities, particularly in patients with Diabetes Mellitus (DM). C-Reactive Protein (CRP) is an inflammatory biomarker, while D-Dimer reflects coagulation activation and fibrinolysis. In COVID-19 patients with DM, both biomarkers may increase due to chronic inflammation, hyperglycemia, endothelial dysfunction, and a prothrombotic state. This study aimed to analyze the correlation between D-Dimer and CRP levels in confirmed COVID-19 patients with comorbid Diabetes Mellitus at Haji Hospital Jakarta. This was an observational analytic study with a cross-sectional design using secondary data from medical records of hospitalized COVID-19 patients with DM at Haji Hospital Jakarta from June to September 2021. Total sampling was applied. A total of 80 patients who met the inclusion and exclusion criteria were included in the analysis. The main variables were D-Dimer and CRP levels. Descriptive analysis was used to describe subject characteristics, while the Spearman correlation test was used to assess the correlation between D-Dimer and CRP because the data were not normally distributed. Among 80 subjects, 44 patients (55.0%) were male, and 36 patients (45.0%) were female. The mean age was 55.76 ± 12.28 years, and the mean random blood glucose level was 303.75 ± 70.56 mg/dL. The mean D-Dimer level was 0.96 ± 1.51 µg/mL with a median of 0.50 µg/mL, while the mean CRP level was 58.48 ± 28.59 mg/L with a median of 55.0 mg/L. Elevated D-Dimer levels were found in 41 patients (51.3%), while all subjects (100%) had elevated CRP levels. Spearman correlation analysis showed no significant correlation between D-Dimer and CRP levels (r_s = -0.057; p = 0.618). There was no significant correlation between D-Dimer and CRP levels in COVID-19 patients with comorbid Diabetes Mellitus at Haji Hospital Jakarta. However, both biomarkers may still provide complementary information regarding inflammatory and coagulation status abnormalities in COVID-19 patients with DM.